Scheduling practices for pregnant emergency medicine residents. Issue 6 (21st November 2022) - MacVane, Casey Z.; Puissant, Madeleine; Fix, Megan; Strout, Tania D.; Bonney, Caitlin; Welsh, Laura; Mittelman, Andrew; Ricker, Jana; Agarwal, Isha
Abstract: Background: Night shift work is associated with adverse pathophysiologic effects on maternal and fetal well‐being. Although emergency medicine (EM) residents work frequent night shifts, there is no existing guidance for residency program directors (PDs) regarding scheduling pregnant residents. Our study assessed scheduling practices for pregnant EM residents, differences based on program and PD characteristics, barriers and attitudes toward implementing a formal scheduling policy, and PDs' awareness of literature describing adverse effects of night shifts on maternal–fetal outcomes. Methods: We conducted an anonymous, web‐based survey of U.S. EM residencies ( N  = 276). Quantitative data were summarized; chi‐square analysis and logistic regression were used to assess relationships between program and PD characteristics and schedule accommodations. Qualitative description was used to analyze an open‐ended question, organizing findings into major and minor themes. Results: Of the 167 completed surveys (response rate 61%), 67% of programs reported no formal policy for scheduling pregnant residents but made adjustments on an individual basis including block changes (85%), decreased (46%) or no night shifts (34%), and working shifts earlier in pregnancy to cover later shifts (20%). Barriers to adjustments included staffing constraints (60%), equity concerns (45%), or impact on wellness (41%) among all residents and privacy (28%). PDs endorsed scheduling adjustments as important (mean 8.1, 0–10 scale) and reported guidance from graduate medical education governance would be useful (60%). Larger program size, but not PD gender or proportion of female residents, was associated with an increased likelihood of scheduling modifications. Twenty‐five percent of PDs reported little knowledge of literature regarding night shift work and pregnancy. Qualitative themes supported quantitative findings. Conclusions: Most EM residency programs do not have formal scheduling policies for pregnant residents, but most PDs support making adjustments and do so informally. More education and guidance for PDs are needed to promote the development of formal policies.